"Srela mi te dobra sreggia". Examples of Budva Wedding Songs and Honorific Verses from the Mid-17th Century - Mitić, Kristina R.; Mitrović, Katarina S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper sheds light on the rostave (wedding songs) and počasnice (honorific verses), which represent a unique addition to the third book of The Budva Annals, recorded by Budva nobleman Don Krsto Ivanović (1628–1688), a canon of the Cathedral of Saint John, a municipal teacher, and a chancellor of the apostolic vicariate. This third book of The Budva Annals contains seven chapters devoted to traditional clothing worn by the people of Budva, the emergence of new fashion styles, customs related to the birth of male and female children, engagement celebrations, wedding ceremonies, funeral rites, an both family and public festivities. These lyrical miniatures were written in the vernacular, but using Italian orthography. While most were performed during wedding ceremonies, they were not limited to that context; their themes and content went beyond this scope and were also performed on other occasions.
Keywords: Don Krsto Ivanović; The Budva Annals; customs of toasting; sung toasts